The Intergenerational Transfer of Solar Radiation Management Capabilities and Atmospheric Carbon Stocks - Timo Goeschl; Daniel Heyen; Juan Moreno-Cruz (University of Heidelberg, Department of Economics, 2013)
Solar radiation management (SRM) technologies are considered one of the likeliest forms of geoengineering. If developed, a future generation could deploy them to limit the damages caused by the atmospheric carbon stock inherited from the current generation, despite their negative side effects. Should the current generation develop these geoengi-neering capabilities for a future generation? And how would a decision to develop SRM impact on the current generation's abatement efforts? Natural scientists, ethicists, and other scholars argue that future generations could be more sanguine about the side effects of SRM deployment than the current generation. In this paper, we add economic rigor to this important debate on the intergenerational transfer of technological capabilities and pollution stocks. We identify three conjectures that constitute potentially rational courses of action for current society, including a ban on the development of SRM. How-ever, the same premises that underpin these conjectures also allow for a novel possibility: If the development of SRM capabilities is sufficiently cheap, the current generation may for reasons of intergenerational strategy decide not just to develop SRM technologies, but also to abate more than in the absence of SRM.
urn:nbn:de:bsz:16-heidok-143739
Keywords: 330; Geoengineering; Climate Change; Intergenerational Issues; Strategic Behavior